2013
DOI: 10.1002/mus.23756
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short‐term resistance training and subsequent detraining on the electromechanical delay

Abstract: It can be hypothesized that increases in strength observed after a short-term resistance training program may not be attributed to stiffness changes in the series-elastic component.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…and Stock et al ., however, reported no training‐induced changes in EMD after 7 and 4 weeks of DCER or sprint training, respectively. Although there have been conflicting findings regarding the ability to identify training‐induced adaptations in EMD, our study suggests that EMD E‐F , EMD E‐M , and EMD M‐F may be useful for examining peripheral fatigue. Specifically, the time‐point at EMD E‐F becomes greater than the initial repetitions EMD value may reflect the onset of peripheral fatigue and the time‐course of changes in EMD E‐M , and EMD M‐F may indicate fatigue‐induced changes in excitation–contraction coupling and the series elastic component, respectively.…”
Section: Discussionmentioning
confidence: 75%
“…and Stock et al ., however, reported no training‐induced changes in EMD after 7 and 4 weeks of DCER or sprint training, respectively. Although there have been conflicting findings regarding the ability to identify training‐induced adaptations in EMD, our study suggests that EMD E‐F , EMD E‐M , and EMD M‐F may be useful for examining peripheral fatigue. Specifically, the time‐point at EMD E‐F becomes greater than the initial repetitions EMD value may reflect the onset of peripheral fatigue and the time‐course of changes in EMD E‐M , and EMD M‐F may indicate fatigue‐induced changes in excitation–contraction coupling and the series elastic component, respectively.…”
Section: Discussionmentioning
confidence: 75%
“…Kubo et al [30] found that 12 weeks of isometric knee extension training led to decreases in EMD associated with increases in tendon stiffness and rate of torque development. However, Costa et al [14] did not find EMD improvements after very short isokinetic vs. dynamic constant external resistance knee extension training. Similarly, Häkkinen and Komi [22] were unable to find changes in EMD after 16 weeks of dynamic knee extensor training.…”
Section: Emd (Ms)mentioning
confidence: 90%
“…Finally, RT individuals, when compared to endurance athletes, have been found to have shorter EMD [53], which represents the time between the onset of electrical activity at the muscle and the onset of torque, and is positively related to stiffness changes in the serieselastic component [10,30,31]. Nevertheless, RT involving concentric and eccentric muscle actions have not been found to be effective in decreasing EMD [14,22].…”
Section: Introductionmentioning
confidence: 99%
“…Beck et al, (2007) suggested that responses to training might be influenced by the number of training sessions, training volume, and muscle(s) being tested [3]. Nevertheless, Akima et al, (1999) and Costa et al, (2013) suggested future studies should investigate the precise mechanisms underlying strength gains obtained with short-term resistance training [7,43].…”
Section: Discussionmentioning
confidence: 99%